1950
DOI: 10.1085/jgp.33.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acids and Nucleic Acid Content of Cell Nuclei Isolated by a Modification of Behrens' Technique

Abstract: It has already been found that a considerable number of enzymes occur in nuclei of rat liver cells which have been isolated at pH 6.0 by a procedure involving the use of the Waring blendor with very dilute citric acid for breaking the cells, followed by differential centrifugation (1-3). As a complementary type of work, studies have been started to determine the relative concentrations of some important substrates in the cell nucleus as compared to the corresponding concentrations in the whole cell or in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1952
1952
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…I1 liver tissue after removal of tumour nodules. DISCUSSION Our values for the average DNAP content/nucleus in normal adult rat liver (Table 1) are in fairly good agreement with those obtained by other workers using similar methods (Dounce, Tishkoff, Barnett & Freer, 1950;Ely & Ross, 1951a;Harrison, 1951;Leuchtenberger et al 1951;Campbell & Kosterlitz, 1952;and Leuchtenberger et al 1952). To calculate the DNA content/liver nucleus Price and his coworkers determined the amount of DNA/100 g. fresh liver and divided this figure by the number of nuclei/100 g., estimated by nuclear counts on a homogenate of a weighed portion of tissue (Price, Miller, Miller & Weber, 1950;Price & Laird, 1950).…”
Section: Composition Of Whole Liver Tissuesupporting
confidence: 90%
“…I1 liver tissue after removal of tumour nodules. DISCUSSION Our values for the average DNAP content/nucleus in normal adult rat liver (Table 1) are in fairly good agreement with those obtained by other workers using similar methods (Dounce, Tishkoff, Barnett & Freer, 1950;Ely & Ross, 1951a;Harrison, 1951;Leuchtenberger et al 1951;Campbell & Kosterlitz, 1952;and Leuchtenberger et al 1952). To calculate the DNA content/liver nucleus Price and his coworkers determined the amount of DNA/100 g. fresh liver and divided this figure by the number of nuclei/100 g., estimated by nuclear counts on a homogenate of a weighed portion of tissue (Price, Miller, Miller & Weber, 1950;Price & Laird, 1950).…”
Section: Composition Of Whole Liver Tissuesupporting
confidence: 90%
“…Nuclei then sediment towards the bottom of the tube during centrifugation, but lighter components, such as cytoplasmic organelles, whole cells, erythrocytes, and nuclei with tabs of cytoplasm float to the surface. This principle was first applied in nonaqueous procedures (8)(9)(10)(11) and was subsequently adapted to aqueous methods by the use of 2.2 M sucrose (12)(13)(14)(15)(16)(17)(18)(19)(20). These methods appeared to give satisfactory preparations of nuclei, although the yields were often low (16,17) and the methods were difficult to adapt to the processing of large quantities of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The technique involving mechanical disruption of cells and repeated washings with sucrose solutions was adopted after preliminary studies with adenovirushifected HeLa cells showed that this procedure gave better results than other methods tested. Several other techniques were discarded when it was found that the yield of nuclei was too low or that adenovirus was inactivated during the procedure (18)(19)(20)(21). The method employed was originally described by Schneider and Hogeboom (13) and used successfully by Ackermann and Kurtz (22) and Gray and Scott (14) in studies of the intracellular localization of herpes simplex virus in the liver of the mouse or chick embryo.…”
Section: Discussionmentioning
confidence: 99%